Stunning males and powerful females : gender and tradition in East Javanese dance - Sunardi, Christina (University of Illinois Press, 2015)
Christina Sunardi ventures into the regency of Malang in east Java to study and perform with dancers. Through formal interviews and casual conversation, Sunardi learns about their lives and art. Her work shows how performers continually transform dance traditions to negotiate, and renegotiate, the boundaries of gender and sex - sometimes reinforcing lines of demarcation, sometimes transgressing them, and sometimes doing both simultaneously.
Keywords: Folk dancing, Javanese -- Indonesia -- Java.; Dance -- Indonesia -- Java.; Dance -- Social aspects -- Indonesia -- Java.; Dance -- Sex differences.; Java (Indonesia) -- Social life and customs.; Danse folklorique javanaise -- Indonésie -- Java.; Danse -- Indonésie -- Java.; Danse -- Aspect social -- Indonésie -- Java.; Danse -- Différences entre sexes.; Java (Indonésie) -- Mœurs et coutumes.; GAMES -- Reference.; GAMES -- Travel Games.; MUSIC -- Genres & Styles -- Dance.; Dance; Dance -- Sex differences; Dance -- Social aspects; Folk dancing, Javanese; Manners and customs; Indonesia -- Java; Geschlechterforschung; Transgender; Tanztheater; Tanz; Ritual; Männlichkeit; Weiblichkeit; Indonesien; Java -- Ost